Analysis of Indonesia Bond’s Duration: Corporate Versus Government Bond - Rezki Adhitia; Adler Haymans Manurung (Bina Nusantara University, 2009)
The duration of a bond is a measure of its interest rate risk. The objective of this research is to test whether corporate bond duration is higher compare to government bonds. The higher duration mean that bond’s price is more affected to the change in its yield. Effective Duration and Modified Duration Approaches are used to calculate the duration. The sample used is bonds that traded in Indonesia Stock Exchange. The result shows that there is no enough evidence that Indonesia corporate bonds duration is higher compare to government bonds. The implication for this is that there is no difference in interest rate risk between corporate bonds and government bonds.